Effectiveness of peer support to increase uptake of retinal examination for diabetic retinopathy: study protocol for the DURE pragmatic cluster randomized clinical trial in Kirinyaga, Kenya - Nyawira Mwangi; Mark Ng'ang'a; Esbon Gakuo; Stephen Gichuhi; David Macleod; Consuela Moorman; Lawrence Muthami; Peter Tum; Atieno Jalango; Kibata Githeko; Michael Gichangi; Joseph Kibachio; et al. (BMC, 2018)
Abstract Background All patients with diabetes are at risk of developing diabetic retinopathy (DR), a progressive and potentially blinding condition. Early treatment of DR prevents visual impairment and blindness. The natural history of DR is that it is asymptomatic until the advanced stages, thus annual retinal examination is recommended for early detection. Previous studies show that the uptake of regular retinal examination among people living with diabetes (PLWD) is low. In the Uptake of Retinal Examination in Diabetes (DURE) study, we will investigate the effectiveness of a complex intervention delivered within diabetes support groups to increase uptake of retinal examination. Methods The DURE study will be a two-arm pragmatic cluster randomized clinical trial in Kirinyaga County, Kenya. Diabetes support groups will be randomly assigned to either the intervention or usual care conditions in a 1:1 ratio. The participants will be 700 PLWD who are members of support groups in Kirinyaga. To reduce contamination, the unit of randomization will be the support group. Peer supporters in the intervention arm will receive training to deliver the intervention. The intervention will include monthly group education on DR and individual member reminders to take the eye examination. The effectiveness of this intervention plus usual care will be compared to usual care practices alone. Participant data will be collected at baseline. The primary outcome is the proportion of PLWD who take up the eye examination at six months. Secondary outcomes include the characteristics of participants and peer supporters associated with uptake of eye examination for DR. Intention-to-treat analysis will be used to evaluate the primary and secondary outcomes. Discussion Eye care programs need evidence of the effectiveness of peer supporter-led health education to improve attendance to retinal screening for the early detection of DR in an African setting. Given that the intervention combines standardization and flexibility, it has the potential to be adopted in other settings and to inform policies to promote DR screening. Trial registration Pan African Clinical Trial Registry PACTR201707002430195, registered 25 July 2017, www.pactr.org